Expat Nostalgia: Nostalgic Emotions among ‘Permanent Tour ists’ in Pattaya, Thailand - Jacobsen , Michael Hviid (South Asian Journal of Social Sciences and Humanities, 2021)
In a globalized world, the ability to travel and settle elsewhere than one’s native country is an oppor tunity open to still more people. Particularly with the rise of ‘retirement migration’ or ‘lifestyle migra tion’, increasing numbers of senior members move to foreign destinations in order to live the remain ing parts of their lives. The reasons for leaving their home countries in the first place are diversified as are also their experienced upon arrival. However, nostalgia is an identifiable emotion among many  expats or, in this article called ‘permanent tourists’, who may experience a longing for what they left  behind. Based on a study in the city of Pattaya, Thailand, the author by way of informal meetings and  conversations with Western expatriates explored their experiences of nostalgia as an everyday emotion relating to different parts of their lives and memories. The article shows how nostalgia is far from  a one-dimensional emotional response to changing life-circumstances, but rather encompasses a varie ty of connotations, expressions and experiences.
Keywords: Expatriates; Pattaya; nostalgia for one’s homeland; nostalgia for one’s past; nostalgia for the past of one’s present home